PENGARUH PEMBENTUKAN KARANG TARUNA TERHADAP KARAKTER PEMUDA DI DESA PEKADAN KECAMATAN GALIS KABUPATEN BANGKALAN - Mukhlis; Soenardjo; Anindita Trinura Novitasari (Penerbit STKIP PGRI Bangkalan, 2019)
This research was conducted to determine the effect of the existence of youth groups on the character of youth in the village of Pekadan, Galis district, Bangkalan district. The approach used in this study is a quantitative approach with 25 respondents. Based on the results of the t-test hypothesis with the SPSS version 21 program, the results of the t count were 0.112 smaller than t table 0.2068 and a significant probability of 0.912> 0.05, which means that Ha was rejected, Ho was accepted, meaning that the existence of young cadets had no effect on the character of Pekadaan village youth Galis district Bangkalan district.